Astraeus IV: quantifying the star formation histories of galaxies in the Epoch of Reionization. Issue 1 (25th October 2021) - Legrand, Laurent; Hutter, Anne; Dayal, Pratika; Ucci, Graziano; Gottlöber, Stefan; Yepes, Gustavo
ABSTRACT: We use the astraeus framework, which couples an N- body simulation with a semi-analytic model for galaxy formation and a semi-numerical model for reionization, to quantify the star formation histories (SFHs) of galaxies in the first billion years. Exploring four models of radiative feedback, we fit the SFH of each galaxy at z > 5 as log(SFR(z )) = − α (1 + z ) + β ; star formation is deemed stochastic if it deviates from this fit by more than Δ _SFR=0.6 dex. Our key findings are as follows: (i) The fraction of stellar mass formed and time spent in the stochastic phase decrease with increasing stellar mass and redshift z . While galaxies with stellar masses of M_10^7M_ at z ∼ 5 (10) form 70 per cent (20 per cent) of their stellar mass in the stochastic phase, this reduces to 10 per cent at all redshifts for galaxies with M_10^10M_ ; (ii) the fractional mass assembled and lifetime spent in the stochastic phase do not significantly change with the radiative feedback model used; and (iii) at all redshifts, α increases (decreases for the strongest radiative feedback model) with stellar mass for galaxies with M_10^8.5M_ and converges to ∼0.18 for more massive galaxies; β always increases with stellar mass. Our proposed fits can reliably recover the stellar masses and mass-to-light ratios for galaxies with M_10^8\!-\!10^10.5 M_ and M_UV-17 to -23 at z ∼ 5–9. This physical model can therefore be used to derive the SFHs for galaxies observed by a number of forthcoming instruments.